The Development of Guidance Counselling Program through Teaching and Learning Activities for Improving Self-Determination of Students with Intellectual Disability - Jon Efendi (Department of Special Education, 2019)
The autonomy of mild intellectually disabled children is their capabilities to help themselves (self-help). The result of this research is a teacher program which guides autonomy for the mild intellectually disabled students. The research was conducted through the action research approach resulting in “Autonomy Guidance Program” which was arranged collaboratively with teachers of SPLB-C YPPLB Cipaganti Bandung, and then was examined through a seminar. Autonomy guidance that is provided to mild intellectually disabled students are introduction to their characteristics, self-care, plan their daily activities, guidance to do activities consequently, guidance to make a decision, and practice to think positively. The implementation through some practices that were started at low level, consecutively, give guidance, motivation and control that need the participation and cooperation of students’ parents, teachers, and other experts.